Evaluación de los indicadores zootécnicos en toretes mestizos holstein friesian castrados y enteros bajo el efecto del clorhidrato de ractopamina con alimentación similar a pastoreo en la hacienda Moreta - Chancusig Tuso, Juan Carlos (2015)
This research was conducted in the province of Cotopaxi, Sigchos Canton, Parish Chugchilán, Sector Moreta. The main objective of this research was to evaluate the livestock indicators in young bulls castrated and entire under the effect of ractopamine hydrochloride with similar grazing in Moreta hacienda power, in which the variables as animal weight was determined, weight gain, feed intake, feed conversion and economic analysis. This research was performed using a 2 x 2 factorial arrangement implementing a DCA (Completely Randomized Design); As Factor A (Management steers) Neutered and whole, as Factor B (Using Ractopamine) with and without represented as follows....